2007
DOI: 10.1111/j.1745-7270.2007.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Cucumber Mosaic Virus and Zucchini Yellow Mosaic Virus on <italic>Cucurbitaceae</italic> Hosts Tested by Real-time Reverse Transcription-Polymerase Chain Reaction

Abstract: Cucumber mosaic virus (CMV) and zucchini yellow mosaic virus (ZYMV) are two principal viruses infecting cucurbitaceous crops, and their synergy has been repeatedly observed. In our present work, a real-time reverse transcription-polymerase chain reaction procedure was established to study the accumulation kinetics of these two viruses in single and combined infections at the molecular level. The accumulations of open reading frames (ORFs) for 1a, 2a, 3a and coat protein (CP) of CMV and CP of ZYMV were tested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
(24 reference statements)
0
15
0
5
Order By: Relevance
“…Also, it is well known that mixed infections are common in cucurbits (Ali et al 2012), as well as that CMV and potyviruses infecting cucurbits cause a notable symptom enhancement (Massumi et al 2007;Ramos et al 2003) due to synergistic effects (Wang et al 2002;Zeng et al 2007). In this investigation, it was found that the variation of symptoms was great, and not dependent upon the host plant genotype.…”
Section: Discussionmentioning
confidence: 76%
“…Also, it is well known that mixed infections are common in cucurbits (Ali et al 2012), as well as that CMV and potyviruses infecting cucurbits cause a notable symptom enhancement (Massumi et al 2007;Ramos et al 2003) due to synergistic effects (Wang et al 2002;Zeng et al 2007). In this investigation, it was found that the variation of symptoms was great, and not dependent upon the host plant genotype.…”
Section: Discussionmentioning
confidence: 76%
“…However, just focusing on plant viruses, the same interaction described here has been observed for several other pairs of viruses (Hii et al, 2002;Kokkinos & Clark, 2006;Zeng et al, 2007;Wintermantel et al, 2008). In other interactions, however, both viruses gain an advantage (Scheets, 1998;Hii et al, 2002), both viruses pay a cost (Wintermantel et al, 2008), one of them gains whereas the other is not apparently affected (Wang et al, 2002(Wang et al, , 2004Wege & Siegmund, 2007) or one pays a cost whilst the other remains unaffected (Pohl & Wege, 2007).…”
Section: Biological Game Between Tumv and Camv Predicts Exclusion Of mentioning
confidence: 76%
“…Detection techniques used in most previous reports on mixed infections have been aimed at comparing the accumulation of each competing virus in singly versus coinfected plants, but to our knowledge, relative accumulation among competing viruses has been estimated only in a few instances (Scheets, 1998;Kokkinos & Clark, 2006;Zeng et al, 2007;Wintermantel et al, 2008). To determine an estimate of the relative fitness of our competing viruses, TuMV was titrated by RT-qPCR and CaMV by qPCR using an absolute quantification method.…”
Section: Co-infection Exerts Opposite Effects On Tumv and Camv Accumumentioning
confidence: 99%
“…A total of 14 virus-virus interactions out of 9 papers that contained data on the short term and long term quantifications of the viruses were investigated [2], [15], [17][23]. The earliest data reported in those papers was taken as short term data, while the latest data as long term data.…”
Section: Resultsmentioning
confidence: 99%
“…These mixed infections usually generate effects that are not observed in single infections as plants are often found to be co-infected with multiple viruses [1]. The synergy ranges from mutual increase in virus titre, asymmetric increase in titre of one virus, while no change for another virus [2][3], to no change for one virus but asymmetric decrease in titre of the other virus [4]. There have been cases of mutual interference, which causes a decrease in both viruses [5].…”
Section: Introductionmentioning
confidence: 99%